Simulation on off grid hybrid PV-battery system - Mohamed, Mohamed Yusuf (2021)
With the growing usage of renewable energy sources (RES), solar photovoltaic (PV) systems have seen a considerable increase in their use over the last three decades, moving from freestanding to utility-connected PV systems. Off-grid is a type of power distribution system that makes use of renewable energy and is powered by a hybrid PV battery system. In this project the simulation on off grid hybrid PV battery system have been discussed. The system is modelled and simulate in MATLAB Simulink where a PV array with MPPT is connected to the DC bus with a battery storage system of 720 kWh, the performance of the PV system results shows an efficient MPPT where the modules output power at solar irradiance and ambient temperature of 1000 and 1500 W/m2 and 25 C temperature maintained at 2750 W which shows the MPPT efficiency is 98%.